1987
DOI: 10.1017/s0021859600080023
|View full text |Cite
|
Sign up to set email alerts
|

Oestrous and ovarian activity of subtropical fat-tailed Rahmani sheep and their response to light treatment

Abstract: Oestrous and ovarian activity were studied throughout the year in 29 subtropical Rahmani ewes using both vasectomized rams and intravaginal electrical resistance measurements. Percentages of ewes in oestrus and of ewes ovulating were consistently high throughout the year with a detectable drop in spring months. The drop was more pronounced and lasted longer in oestrous activity than in ovarian activity. About 33% of the ewes showed continuous ovarian activity throughout the year while almost all ewes had perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Early in the eighties of last century, an interest trial was carried out by Animal Production Research Institute to establish a nucleus herd of Zaraibi goats, and series of studies had been carried on. Aboul-Ela et al (1988) reported variable ovulation rates, ranging from 1 to 6, with a mean of 2.6 ova's. Abdel-Raheem (1998.…”
Section: Main Local Breeds Zaraibi Goat (Egyptian Nubian)mentioning
confidence: 99%
“…Early in the eighties of last century, an interest trial was carried out by Animal Production Research Institute to establish a nucleus herd of Zaraibi goats, and series of studies had been carried on. Aboul-Ela et al (1988) reported variable ovulation rates, ranging from 1 to 6, with a mean of 2.6 ova's. Abdel-Raheem (1998.…”
Section: Main Local Breeds Zaraibi Goat (Egyptian Nubian)mentioning
confidence: 99%
“…However, Aboul-Naga and Aboul-Ela (1984) attributed this effect to inherited internal physiological rhythm determining the cycling activity of a ewe under a given environmental condition. However, Mousa (1986), Aboul-Naga et al (1987), Lahlou-Kassi and Boukhliq (1988) and Aboul-Ela and Chaemineau (1989) working on different subtropical fattailed ewes reported that the seasonal changes in oestrous and ovulation activity could be attributed to changes in daylength. The authors mentioned that a strong relationship existed between oestrous activity and reproductive performance of subtropical sheep flocks.…”
Section: A-fertility Traits: Conception Rate (Cr)mentioning
confidence: 99%